2022
DOI: 10.3390/cells11172646
|View full text |Cite
|
Sign up to set email alerts
|

ResSUMO: A Deep Learning Architecture Based on Residual Structure for Prediction of Lysine SUMOylation Sites

Abstract: Lysine SUMOylation plays an essential role in various biological functions. Several approaches integrating various algorithms have been developed for predicting SUMOylation sites based on a limited dataset. Recently, the number of identified SUMOylation sites has significantly increased due to investigation at the proteomics scale. We collected modification data and found the reported approaches had poor performance using our collected data. Therefore, it is essential to explore the characteristics of this mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…The characteristics of AAs in the protein fragment were shown to be an important parameter with which to predict sumoylation sites ( Khan et al, 2021 ) according to the large proportion of TF3. All of the features in TF4 were part of the optimal feature set, indicating that the features of the local region of peptide play a critical role in the recognition of sumoylation sites ( Zhu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of AAs in the protein fragment were shown to be an important parameter with which to predict sumoylation sites ( Khan et al, 2021 ) according to the large proportion of TF3. All of the features in TF4 were part of the optimal feature set, indicating that the features of the local region of peptide play a critical role in the recognition of sumoylation sites ( Zhu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, computational approaches can be clustered into sequence-based and structure-based groups. Structure-based methods incorporate learning algorithms with sequence features derived from BLOSUM62 ( Xu et al, 2016 ; Zhu et al, 2022 ), pseudo amino acid composition (PseAAC) ( Jia et al, 2016 ), position relative incidence matrix (PRIM) ( Khan et al, 2021 ), etc. Structure-based methods integrate learning algorithms with physical features retrieved from local geometric information, such as half-sphere exposure (HSE) ( Sharma et al, 2019 ), backbone torsion angles, accessible surface area (ASA) ( Lopez et al, 2020 ), and contact number (CN) ( Dehzangi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many classifiers for predicting various types of PTM sites have been developed by integrating machine-learning or deep-learning algorithms with different encoding features ( Chen et al, 2018a ; Huang et al, 2018 ; Chen et al, 2019 ; Lyu et al, 2020 ; Zhang et al, 2020 ; Zhao et al, 2020 ; Sha et al, 2021 ; Wei et al, 2021 ; Zhu et al, 2022 ). It has been found that the models based on deep-learning algorithms have better prediction performances than those based on traditional machine-learning algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we divided the data randomly into 10 groups: 9/10 (i.e., 702 positives and 702 negatives) as the cross-validation dataset and 1/10 (i.e., 78 positives and 78 negatives) as the independent test dataset. The data frame sample function in the pandas Python library was used for random number generation [33].…”
Section: Benchmark Datasetmentioning
confidence: 99%